Production of chitin and chitosan from shrimp shell wastes - Islam, SZ; Khan, M; Alam, AKM Nowsad (Journal of the Bangladesh Agricultural University, 2017)
A method was developed for commercial scale production of chitin and chitosan in Bangladesh from marine shrimp, P. monodon and freshwater prawn, M. rosenbergii shell and appendages. Chitin is a macro-molecular linear polymer of anhydro N-acetyl glucosamine (N-Acetyl, 2-Amino 2-Deoxy DGlucose) and chitosan is deacetylated chitin. For production of chitin, fresh shells of P. monodon having initial bacterial load of >105 CFU/g sample and peroxide values of >10 mmol free iodine liberated /kg of oil were washed with dilute sulfuric acid. Adhered proteins were removed by washing with low strength alkaline solution and then rinsed with water. Crude chitin thus prepared was treated with concentrated hydrochloric acid and purified chitin was obtained after treating with low strength alkali solution. Water soluble chitosan was prepared by performing a deacetylation process using 50% NaOH (w/w) at 100oC for 4-5 hours and then washed, dried and ground. For purification of chitin and chitosan, a series of experiments were conducted to optimize the level of NaOH concentration and time and temperature schedule of demineralization and deproteinization/deacetylation. A high temperature-short time schedule obtained best quality chitin and chitosan. Both subjective and objective methods were used for the testing of quality and purity of chitin and chitosan. Comparative studies between the quality of products from different components of the shell and from different shrimp/prawn species showed that both chitin and chitosan obtained from M. rosenbergii shell were better compared to those of P. monodon in terms of extractability, deacetylation, and color. Shells obtained better product compared to shrimp appendages. The study suggests that chitin and chitosan can be produced in existing shrimp/prawn processing plants of the country with the simple renovation. J. Bangladesh Agril. Univ. 14(2): 253-259, December 2016